Do former elite athletes live longer? Potential role of critical window(s) in the development of the health-oriented behaviors and physiological adaptations - Kujawska, Agnieszka; Topka, Weronika; Gajos, Małgorzata; Androsiuk-Perkowska, Joanna; Perkowski, Radosław; Husejko, Jakub; Marszałek, Agata; Szczęśniak, Żaneta; Cieślińska, Aleksandra; Skierkowska, Natalia; et al. (Journal of Education, Health and Sport, 2017)
Introduction: Some epidemiological data indicate that moderate-to-vigorous levels of physical activity could be beneficial for longevity. Moreover, in terms of cognitive functioning, mental activities undertaking during first decades of life translate to better coping with pathological changes of brain during aging. Therefore, it is worth to examine the relationship between the most intense form of regular physical exercise undertaking, which is typical for the former elite athletes, with longevity. Material and methods: Articles in the EBSCO database have been analyzed using keywords: longevity, ex-elite athletes, former elite athletes, ex-athletes, mortality, chronic diseases. Results: Reviewed literature described the longevity of participants who were active elite athletes. Analyzed groups could be separated based on sport type: aerobic, anaerobic and mixed, and due to, inter alia, sex and race of sportsmen. Conclusions: There is some evidence for increased longevity in the former elite athletes of aerobic and mixed sports and for decreased longevity in anaerobic, comparing to general population. However, there is need for further studies with design which could explain the mechanism of differences in longevity and incorporate potentially confounding factors.